Mobilising the non-physical benefits of participation in a rural physical activity event: parkrun - Paul Goldschagg (Social Sciences and Humanities Open)
Whilst the physical and mental health benefits of regular exercise are well documented, their non-physical benefits remain less understood. Although not originally envisaged, these benefits can positively influence participant's socioeconomic circumstances. This study explores the perceived non-physical benefits of adolescent and young adult runner/walker/volunteer participation in a weekly parkrun event held in rural South Africa, considered through the lens of social capital analysis. Ten semi-structured interviews were conducted to explore perceptions of the non-physical benefits of participation. Using topic analysis, four key topics emerged: a) mentoring, care and life skills as pillars of life skill development; b) strengthening and practising language skills; c) acquiring digital literacy skills; d) receiving donations of running kit, all of which reflect valuable non-physical benefits for youth in this rural setting. These findings contribute to the literature on the role of social capital in community development by highlighting how bonding capital (local relationships) and bridging capital (connections to broader networks) can be fostered through a seemingly simple active leisure event. Although not intended for socioeconomic upliftment, this parkrun has created meaningful pathways for youth development. Improving the lives of the youth requires much more than a reliance on government. Ensuring a steady flow of context specific assistance from both government departments and outside organisations is a necessary condition for successful socioeconomic development.